2018
DOI: 10.1039/c8qi00085a
|View full text |Cite
|
Sign up to set email alerts
|

Simple surface-assisted formation of palladium nanoparticles on polystyrene microspheres and their application in catalysis

Abstract: Herein we develop a facile and green method for assembling palladium nanoparticles on polystyrene microsphere with excellent catalytic performance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These values were consistent with Pd(0) binding energy, indicating that Pd( ii ) has been successfully reduced to Pd(0) by LNT. 20 Kardanpour and coworkers prepared highly dispersed Pd NPs which had similar binding energy compared with Pd 150 -LNT NPs. 21 Therefore, XPS results confirmed the successful preparation of Pd n -LNT NPs.…”
Section: Resultsmentioning
confidence: 99%
“…These values were consistent with Pd(0) binding energy, indicating that Pd( ii ) has been successfully reduced to Pd(0) by LNT. 20 Kardanpour and coworkers prepared highly dispersed Pd NPs which had similar binding energy compared with Pd 150 -LNT NPs. 21 Therefore, XPS results confirmed the successful preparation of Pd n -LNT NPs.…”
Section: Resultsmentioning
confidence: 99%
“…4.5 nm) that were well dispersed on the PS template microspheres (Figure 1d and 1g). 20 However, the SEM image (Figure 1a) reveals a surface morphology similar to the template microspheres. In contrast, the SEM image (Figure 1b) of the PS/Pd@ZIF-8 composite particles manifests that, each PS/Pd composite particle is encapsulated by a ZIF-8 shell containing some distinguishable rhombic dodecahedron nanocrystal.…”
Section: Characterizationmentioning
confidence: 95%
“…7.0 nm) were successfully incorporated into the ZIF-8 hollow microspheres (Figure 5), by reducing the concentration of PS template microspheres that was added in PdCl 2 aqueous solution during the synthesis of Pd NPs. 20 The first step in the synthetic approach (Scheme 1) is based on our reported work on surface-assisted growth of Pd NPs on PS microspheres. Therein, the PS/Pd composite particles with smaller Pd NPs were found to exhibit higher catalytic activity.…”
Section: Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Among them, polystyrene (PS) particles have shown numerous advantages as a catalytic support material, such as their simple and large scalable synthesis, monodispersity and controllability in size and shape, good dispersion in various media, and easy surface modication. [17][18][19][20] Because most of previously reported studies have used, however, solid PS particles with a relatively low surface area, [20][21][22][23][24][25][26] it is difficult to increase the loading amount of noble metal NPs. Alternatively, numerous studies have reported the fabrication of PS particles with hollow structures to provide large surface areas.…”
Section: Introductionmentioning
confidence: 99%